Menstimulasi Kecerdasan Anak Melalui Permainan Gici-Gici - Didimus Sutanto B Prasetya; Dina Anjely Sinaga; Sintia Wellmy Sopacua (Real Kiddos: Jurnal Pendidikan Anak Usia Dini, 2023)
Early childhood development depends on the ability to stimulate brain neurons (nerves) at age (0-8 years), while brain development stops at the age of 18 years. If neurons are not stimulated, they will experience shrinkage which result in a person’ intelligence level. The crucial peak in providing brain stimulation for children is in the early age range, namely 0-8 years, where at the age of 8 years their development reaches 80 percent. This research aims to find and explain the gici-gici games in stimulating early childhood intelligence. The research method uses descriptive qualitative research. Gici-gici games are traditional educational game that can be used in stimulating early childhood intelligence. As a result, playing gici-gici games can increase multiple intelligences.Keywords: gici-gici game; traditional educational games; early childhood; multiple intelligences; neurologyAbstrakPerkembangan anak usia dini tergantung pada kemampuan menstimulasi neuron (syaraf) otak pada usia (0-8 tahun), sedangkan perkembangan otak berhenti pada usia 18 tahun. Jika neuron tidak terstimulasi, akan mengalami penyusutan yang berakibat pada tingkat kecerdasan seseorang. Puncak krusial dalam memberikan stimulasi otak anak berada pada rentang usia dini, yaitu 0-8 tahun, di mana pada usia 8 tahun perkembangannya mencapai 80 persen. Penelitian ini bertujuan menemukan dan menjelaskan tentang permainan gici-gici dalam menstimulasi kecerdasan anak usia dini. Metode penelitian menggunakan penelitian kualitatif deskriptif. Permainan gici-gici adalah permainan edukatif tradisional yang dapat digunakan dalam menstimulasi kecerdasan anak usia dini. Hasilnya, permainan gici-gici dapat meningkatkan kecerdasan majemuk (multiple intellegences).Kata Kunci:permainan gici-gici; permainan edukatif tradisional; anak usia dini; kecerdasan majemuk; neurologi